Answer:
Part 1) ![z=4\sqrt{3}\ units](https://tex.z-dn.net/?f=z%3D4%5Csqrt%7B3%7D%5C%20units)
Part 2) ![y=4\sqrt{2}\ units](https://tex.z-dn.net/?f=y%3D4%5Csqrt%7B2%7D%5C%20units)
Part 3) ![x=4\sqrt{6}\ units](https://tex.z-dn.net/?f=x%3D4%5Csqrt%7B6%7D%5C%20units)
Step-by-step explanation:
see the attached figure with letters to better understand the problem
step 1
<em>Find the value of z</em>
In the right triangle DBC
----> equation A
In the right triangle ABC
----> equation B
equate equation A and equation B
![\frac{4}{z}=\frac{z}{12}](https://tex.z-dn.net/?f=%5Cfrac%7B4%7D%7Bz%7D%3D%5Cfrac%7Bz%7D%7B12%7D)
![z^{2}=48](https://tex.z-dn.net/?f=z%5E%7B2%7D%3D48)
![z=4\sqrt{3}\ units](https://tex.z-dn.net/?f=z%3D4%5Csqrt%7B3%7D%5C%20units)
step 2
In the right triangle DBC
Applying the Pythagoras Theorem
![z^{2}=y^{2}+4^{2}](https://tex.z-dn.net/?f=z%5E%7B2%7D%3Dy%5E%7B2%7D%2B4%5E%7B2%7D)
we have
![z=4\sqrt{3}\ units](https://tex.z-dn.net/?f=z%3D4%5Csqrt%7B3%7D%5C%20units)
substitute
![(4\sqrt{3})^{2}=y^{2}+4^{2}](https://tex.z-dn.net/?f=%284%5Csqrt%7B3%7D%29%5E%7B2%7D%3Dy%5E%7B2%7D%2B4%5E%7B2%7D)
![48=y^{2}+16](https://tex.z-dn.net/?f=48%3Dy%5E%7B2%7D%2B16)
![y^{2}=48-16](https://tex.z-dn.net/?f=y%5E%7B2%7D%3D48-16)
![y^{2}=32](https://tex.z-dn.net/?f=y%5E%7B2%7D%3D32)
![y=4\sqrt{2}\ units](https://tex.z-dn.net/?f=y%3D4%5Csqrt%7B2%7D%5C%20units)
step 3
Find the value of x
In the right triangle ABC
Applying the Pythagoras Theorem
![12^{2}=x^{2}+z^{2}](https://tex.z-dn.net/?f=12%5E%7B2%7D%3Dx%5E%7B2%7D%2Bz%5E%7B2%7D)
we have
![z=4\sqrt{3}\ units](https://tex.z-dn.net/?f=z%3D4%5Csqrt%7B3%7D%5C%20units)
substitute
![12^{2}=x^{2}+(4\sqrt{3})^{2}](https://tex.z-dn.net/?f=12%5E%7B2%7D%3Dx%5E%7B2%7D%2B%284%5Csqrt%7B3%7D%29%5E%7B2%7D)
![144=x^{2}+48](https://tex.z-dn.net/?f=144%3Dx%5E%7B2%7D%2B48)
![x^{2}=144-48](https://tex.z-dn.net/?f=x%5E%7B2%7D%3D144-48)
![x^{2}=96](https://tex.z-dn.net/?f=x%5E%7B2%7D%3D96)
![x=4\sqrt{6}\ units](https://tex.z-dn.net/?f=x%3D4%5Csqrt%7B6%7D%5C%20units)